Pengaruh Bantuan Langsung Tunai (BLT) Terhadap Kesehatan Masyarakat Dan Perilaku Sosial Di Kelurahan Siantar Simarimbun - Fidia Chairany Sitorus; Muzfirah Filzah; Elsa Dameria Naibaho; Faisal Alviandi Siadari; Fahri Irfarizki Siregar; Tomi Hermanto Damanik; Pawer D. Panjaitan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Direct Cash Assistance (BLT) is a government program that aims to reduce poverty and improve people's welfare. This program provides direct financial assistance to poor families in an effort to meet their basic needs. The purpose of this study was to examine the effect of BLT on public health and social behavior. The research method used in this study is a quantitative approach using survey data from respondents who have received BLT. The data collected included information about the health conditions of the respondents before and after receiving BLT, as well as changes in their social behavior. Statistical analysis was used to identify the relationship between BLT and health and social behavior. The results of this study indicate that the provision of BLT has a significant positive effect on public health. Respondents who received BLT reported increased access to health services, including access to medicines, medical care, and immunization. In addition, there have been improvements in health behaviors, such as better diets, better personal hygiene, and higher levels of physical activity. Apart from health, BLT also had a positive impact on people's social behavior. Respondents reported increases in participation in community activities, awareness of social issues, and involvement in social activities. This shows that acceptance of BLT not only affects individual health conditions, but also strengthens social bonds and community participation.